(untitled) (Research, Society and Development, 2023)
Biochemistry is a subject that is part of the curriculum of undergraduate courses in chemistry and biology. Its presence in the curriculum of these courses consists of offering the student a more detailed learning of the worlds of chemistry and biology that merge to constitute biochemistry. This learning will be used by these graduates to pursue a research career or as future teachers who will work in high school chemistry and biology subjects. As future teachers, these undergraduate students will be drivers of biochemistry knowledge. For this to happen, the professors who teach them need to be familiar with and have affinity with the discipline. Therefore, the present work sought to contextualize how undergraduate students of chemistry and biology courses relate to biochemistry, how their taste for the teaching and learning process of its contents behaves, which themes in biochemistry they elect as important for young people to know . The evaluation was carried out through the application of a questionnaire to the students of the mentioned courses who were in the graduation stage. Students showed a certain relationship of disgust, while understanding the importance of biochemistry. They also reported not having guidance in the discipline of biochemistry in terms of how to work with biochemistry in high school. In this way, we infer that there is a large gap and distancing of knowledge offered at the University to undergraduates and those offered in high school in the disciplines of chemistry and biology with regard to the contextualization of biochemistry.